Analisa Forward dan Inverse Kinematics pada Simulator Arm Robot 5 Derajat Kebebasan - Budi Utomo; Munadi Munadi (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2013)
An arm robot simulator 5 dof (degree of freedom) which is equipped with a two-finger gripper is designed to determine the movement of the robot manipulator. To make an arm robot simulator, we used acrylic as a base material, servomotor as a driver and an Arduino Uno SMD as microcontroller. Acrylic was chosen because it is light, strong and durable. Arduino Uno SMD was chosen because it can interact with LabVIEW that will be able to control the movement angle of servomotor manually. The purpose of this final project is to make an arm robot simulator 5 dof which equipped a gripper and continued with analysis forward and inverse kinematics. An arm robot simulator 5 dof can be used as demonstration tool in education. For making the link of simulator, we use the acrylic laser cutting machine to be more precision cutting. Servomotor’s movement is controlled by using a program that was created using LabVIEW. Servomotor’s angle position error was corrected by using program functions of numerical multiply and numerical divided on LabVIEW. Analysis forward and inverse kinematcis used MATLAB software as a tool for the calculation and we used verification with RoboAnalyzer software. For calculation forward kinematics is required notation Denavit-Hartenberg parameters will result the orientation and position of the end-effector. The orientation and position obtained by transformasi matrix. Then inverse kinematics obtained by performing decrease in transformasi matrix so that is obtained the angle at each joint.